Pendampingan Prosedur Pelayanan Frontliner Menggunakan Aplikasi Patricia Pada KISEL (Koperasi Telkomsel Tap Bogor) - Abdul Roup; Bambang Rahardjo; Rahma Djati Kusuma; Tiffany Aprilly Sopandi Putri (Jurnal Abdimas Dedikasi Kesatuan, 2022)
Service is an activity of interaction between a person both physically and virtually which aims to get customer satisfaction. Service is very important for a company that is still developing to improve the quality of the company and make the company develop for the better. The basic understanding of the service includes the friendliness of employees, willingness to help and knowledge of the products of a company. The purpose of this review is to find out theservice procedure frontliner using the Patricia application at Kisel (Telkomsel Cooperative) TAP Bogor. To achieve clear research objectives, the authors formulate problems regarding the role of service quality, the influence of sales on service and the effect of consumer satisfaction on Kisel services. Based on the research results show that Frontliner has an important role in a service in the company. Good service quality can foster high customer satisfaction. The provision of various payment methods also makes it easier for consumers to make purchase transactions. Keywords: service, frontliner, payment